Surgical Menopause and Estrogen Therapy Modulate the Gut Microbiota, Obesity Markers, and Spatial Memory in Rats - Zeibich, Lydia; Koebele, Stephanie V.; Bernaud, Victoria E.; Ilhan, Zehra Esra; Dirks, Blake; Northup-Smith, Steven N.; Neeley, Rachel; Maldonado, Juan; Nirmalkar, Khemlal; Files, Julia A.; Mayer, Anita P.; Bimonte-Nelson, Heather A.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Menopause in human females and subsequent ovarian hormone deficiency, particularly concerning 17β-estradiol (E2), increase the risk for metabolic dysfunctions associated with obesity, diabetes type 2, cardiovascular diseases, and dementia. Several studies indicate that these disorders are also strongly associated with compositional changes in the intestinal microbiota; however, how E2 deficiency and hormone therapy affect the gut microbial community is not well understood. Using a rat model, we aimed to evaluate how ovariectomy (OVX) and subsequent E2 administration drive changes in metabolic health and the gut microbial community, as well as potential associations with learning and memory. Findings indicated that OVX-induced ovarian hormone deficiency and E2 treatment had significant impacts on several health-affecting parameters, including (a) the abundance of some intestinal bacterial taxa (e.g., Bifidobacteriaceae and Porphyromonadaceae), (b) the abundance of microbial short chain fatty acids (SCFAs) (e.g., isobutyrate), (c) weight/BMI, and (d) high-demand spatial working memory following surgical menopause. Furthermore, exploratory correlations among intestinal bacteria abundance, cognition, and BMI underscored the putative influence of surgical menopause and E2 administration on gut-brain interactions. Collectively, this study showed that surgical menopause is associated with physiological and behavioral changes, and that E2-linked compositional changes in the intestinal microbiota might contribute to some of its related negative health consequences. Overall, this study provides novel insights into interactions among endocrine and gastrointestinal systems in the post-menopausal life stage that collectively alter the risk for the development and progression of cardiovascular, metabolic, and dementia-related diseases.